Getting back to business : why modern portfolio theory fails investors and how you can bring common sense to your portfolio - Peris, Daniel (McGraw-Hill Education, 2018)
Balancing detailed historical evidence with a practitioners real-world expertise, this book asks the right questions?and provides a solution that makes sense in todays challenging investing landscape. --